Effect of Profitability, Leverage, and Liquidity on Company Value with Dividend Policy as A Moderation Variable (In IDX High Dividend Companies 20 Period 2017 – 2021) - Silvia Mutiara Prihanta; Ira Hapsari; Suryo Budi Santoso; Hardiyanto Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of profitability, leverage, and liquidity on company value at IDX High Dividend 20 with a moderating variable, namely dividend policy. The type of data used is secondary data obtained from the IDX and the samples used in this study are companies that are included in the high dividend index criteria for 2017 - 2021 so a sample of 81 is obtained. The sampling technique is purposive sampling with a pooled unbalanced sample or using all samples. existing but not balanced in the number of years. The data analysis method used is Moderated Regression Analysis (MRA). The results of the analysis test show that the effect of profitability, leverage and dividend policy has a positive effect on company value, and liquidity has no effect on company value. In addition, the dividend policy is not able to moderate profitability, leverage, and liquidity on company value.